Serum levels of S100A6 are unaltered in patients with resectable cholangiocarcinoma. Issue 1 (27th September 2016) - Loosen, Sven H.; Benz, Fabian; Niedeggen, Jennifer; Schmeding, Maximilian; Schüller, Florian; Koch, Alexander; Vucur, Mihael; Tacke, Frank; Trautwein, Christian; Roderburg, Christoph; Neumann, Ulf P.; Luedde, Tom
Abstract: Background: Elevated expression levels of S100A6, a calcium‐binding low‐molecular‐weight protein, were demonstrated in various malignancies. Moreover, increased serum levels of S100A6 were suggested as a novel biomarker for various inflammatory and malignant diseases including lung and gastric cancer. However, up to now, serum concentrations of S100A6 have not been analyzed in patients with cholangiocarcinoma (CCA). Methods: S100A6 mRNA expression levels were analyzed in human and murine CCA tumor samples, using semi‐quantitative reverse transcriptase PCR. S100A6 serum concentrations were measured using an enzyme‐linked immunosorbent assay in 112 patients with CCA referred to surgery for curative resection and were compared to those of 42 healthy controls. Results were correlated with clinical data. Results: S100A6 mRNA expression levels were significantly up‐regulated in tumor samples of CCA patients and in tumor tissue of a CCA mouse model. In contrast, serum levels of S100A6 were not significantly altered in patients with CCA compared to healthy controls. Whereas no differences became apparent within the different clinical subgroups of CCA, patients with primary sclerosing cholangitis (PSC)‐based CCA displayed higher levels of S100A6 compared to the other patients. Nevertheless, patients with higher S100A6 serum concentrations showed a trend towards an impaired prognosis compared to patients with lower levels. Finally, within our cohort of patients both the diagnostic and prognostic potentials of S100A6 were similar to those of the clinically established biomarkers CEA and CA19‐9. Conclusion: Although S100A6 was expressed at significantly higher levels in human and murine CCA tumor samples, S100A6 serum levels were not regulated in patients with CCA and are thus not suitable for diagnosis of CCA. However, CCA‐patients with elevated S100A6 displayed a trend toward an impaired prognosis compared to patients with lower S100A6 levels, supporting its further evaluation as a prognostic biomarker in CCA.